(untitled) (World Bulletin of Public Health, 2024)
Malignant tumors of the female reproductive system are one of the serious threats to women’s health. The most common and dangerous of these cancers are cervical cancer (cervical carcinoma), ovarian cancer (ovarian carcinoma), endometrial cancer (endometrial carcinoma), and vulvar cancer. Each of these cancers has specific histological, genetic, and microscopic changes that determine the development of the disease and the effectiveness of treatment. Cervical carcinoma is primarily associated with HPV (Human Papillomavirus) infection, and early detection of this disease can be achieved through diagnostic tools such as the Pap test and HPV test. Ovarian cancer is often diagnosed at later stages and is characterized by a high capacity for metastasis. Histologically, ovarian cancer is classified into serous, endometrioid, and mucinous carcinomas. Endometrial carcinoma predominantly occurs in women after menopause and is generally related to hormonal changes. This disease often begins with unclear bleeding and, when diagnosed early, can be successfully treated. Vulvar cancer occurs in the external genitalia and has specific histological characteristics. Modern diagnostic methods such as ultrasound, CT (computed tomography), MRI (magnetic resonance imaging), and molecular genetic analyses play a crucial role in the early detection of these cancers. Histological examinations and pathological features are also of great importance in determining the best treatment strategy. Treatment for these cancers includes surgery, chemotherapy, and radiation therapy, while new approaches such as molecular therapy and immunotherapy can contribute to improving treatment efficacy.[5;6]